2011
DOI: 10.4038/sjae.v5i0.3475
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nutritional Labeling on Consumer Buying Behavior

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 12 publications
0
22
1
Order By: Relevance
“…The findings of the study revealed that nutritional labeling had less influence in purchase decisions as far as young consumers were considered. Results were in contradiction to the findings of (Prathiraja & Ariyawardana 2003;Kempen et al 2011;Vyth et al, 2010) mentioning nutritional labeling having positive influence on purchase patterns.Out of the ten factors which initially converged after rotation in factor analysis, only three factors namely 'Nutritional Belief', 'Storage instruction & Information overload', and 'Exercise & Nutrition' emerged to be significant after t test and regression analysis results. These factors were mainly inclined outside the purview of nutritional labeling and purchase influence.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…The findings of the study revealed that nutritional labeling had less influence in purchase decisions as far as young consumers were considered. Results were in contradiction to the findings of (Prathiraja & Ariyawardana 2003;Kempen et al 2011;Vyth et al, 2010) mentioning nutritional labeling having positive influence on purchase patterns.Out of the ten factors which initially converged after rotation in factor analysis, only three factors namely 'Nutritional Belief', 'Storage instruction & Information overload', and 'Exercise & Nutrition' emerged to be significant after t test and regression analysis results. These factors were mainly inclined outside the purview of nutritional labeling and purchase influence.…”
Section: Resultscontrasting
confidence: 56%
“…The present study examines young consumers' perceptions ,responses, towards nutritional labeling of food products particularly in South Indian context. Prathiraja and Ariyawardana (2003) mentioned nutritional labeling as an important function in providing pertinent nutrition information to customers. A study which was conducted at three super markets in Sri Lanka to recognize the market for nutritional labeling and the factors that persuade the consumer's willingness-to-pay for nutritional labeling indicated that gender, level of education and special dietary status had a positive effect and the household size had a negative effect on the willingness to pay for nutrition information.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, it has been shown to be a valid instrument to obtain information on the perceived utility of nutritional label for consumers [19], in particular with reference to the European context [20]. Several studies have highlighted the role of labeling in the decision-making process [21].…”
Section: Discussionmentioning
confidence: 99%
“…Theseresults are in line with the study to determine consumer willingness to pay for nutritional labelling by Prathiraja and Ariyawardana (2003) and study examines the factors that influence consumers' perceptions or beliefs about food labels by (Nayga Jr, 1999).…”
Section: People Under Special Dietary Status or Being Vegetarianmentioning
confidence: 48%